THEORETICAL RESEARCH REGARDING THE RISK-FREE WORK OF THE GANTRY CRANES - GHEORGHE N. RADU; IOANA SONIA COMĂNESCU (Journal of Engineering Studies and Research)
The research bases on the observation that the check imposed by the National Authority I.S.C.I.R. regarding the cranes authorization is necessary but not enough for the assurance of their work safety. The current specific rules do not contain provisions concerning the vibratory state of the cranes. Practice shows that the beginning of a work which is outside the normal parameters (changes of the optimum technical state – risk of accidents occurrence), appear in their vibratory mark. The research has as main goal the increase of the work safety and the elimination of the risk of accidents.